Teacher code of ethics - Munawwir, Munawwir; Ummah, Umrotul Khoiroh; Izakiyah, Nurus Shobach (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This research is focused on examining more deeply about the Teacher's Code of Ethics. This study uses a descriptive approach and uses data collection techniques in the form of observation and literature study, namely library research where the sources are obtained through books and journal articles related to the subject of research material. The results and conclusions of this study include: a) The teacher's code of ethics is the values or norms as a unit that aims to regulate and direct how a teacher expresses himself both in attitude and behavior by reinforcing his position and role as well as protecting his profession. b) The teacher's code of ethics can only be established by the highest organization that oversees the teaching profession and applies to bind its members. c) Determination of the code of ethics for teachers may not be done individually or individually. This means that in determining the teacher's code of ethics, it can only be determined if it has been discussed and decided in a joint meeting.